2015
DOI: 10.1111/acps.12543
|View full text |Cite
|
Sign up to set email alerts
|

Conversion to dementia in mild cognitive impairment diagnosed with DSM‐5 criteria and with Petersen's criteria

Abstract: Conversion rate to dementia and AD was higher using DSM-5-MCI criteria than using Petersen's criteria. However, prediction of the construct still has some way to go, as most MCI individuals did not convert at 4.5-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 36 publications
0
25
1
Order By: Relevance
“…The risk estimation found by Gulpers et al [14] was twice as high as what we found in this study and our previous meta-analysis [15]. The main reason for this difference could be that three out of six community samples investigated by Gulpers et al were comprised entirely of individuals with mild cognitive impairment at baseline, and who might have a higher risk of conversion to dementia than cognitively intact subjects [37]. In our meta-analysis, all studies excluded prevalent demented participants, and all but one [13] excluded participants with cognitive impairment at baseline (e.g., measured with the MMSE) or controlled for baseline cognition in the analysis.…”
Section: Comparison With Previous Studiescontrasting
confidence: 69%
“…The risk estimation found by Gulpers et al [14] was twice as high as what we found in this study and our previous meta-analysis [15]. The main reason for this difference could be that three out of six community samples investigated by Gulpers et al were comprised entirely of individuals with mild cognitive impairment at baseline, and who might have a higher risk of conversion to dementia than cognitively intact subjects [37]. In our meta-analysis, all studies excluded prevalent demented participants, and all but one [13] excluded participants with cognitive impairment at baseline (e.g., measured with the MMSE) or controlled for baseline cognition in the analysis.…”
Section: Comparison With Previous Studiescontrasting
confidence: 69%
“…In a large population-based study of 4057 individuals with 4.5 years follow-up, DSM-5 criteria gave a higher annual progression rate than Petersen criteria for progression to Alzheimer's disease dementia and to all-cause dementia. 66 However, the majority of people who developed Alzheimer's disease dementia were classified as normal controls at baseline. The DSM-5 criteria were more restrictive, with only 139 cases meeting criteria, whereas 303 cases met criteria for Petersen aMCI.…”
Section: Subtype and Progression To Alzheimer's Disease Dementiamentioning
confidence: 99%
“…[13][14][15] However, a consensus has been reached that reviewing modifiable factors in daily living would be beneficial for prevention of progression, 16 and that multi-domain intervention is more effective than single domain interventions, including exercise. Thus, in patients with MCI, intervention to prevent conversion to dementia is also important.…”
Section: Mild Cognitive Impairment: Prevention Of Conversion To Dementiamentioning
confidence: 99%
“…The proportion of conversion to dementia and that of reversion to a normal status differ among studies, and related factors are still under research. [13][14][15] However, a consensus has been reached that reviewing modifiable factors in daily living would be beneficial for prevention of progression, 16 and that multi-domain intervention is more effective than single domain interventions, including exercise. The current issues are the choice and combination of target factors.…”
Section: Mild Cognitive Impairment: Prevention Of Conversion To Dementiamentioning
confidence: 99%